2003
DOI: 10.1144/gsl.sp.2003.218.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Arc-trench rollback and forearc accretion: 2. A model template for ophiolites in Albania, Cyprus, and Oman

Abstract: Ophiolite assemblages record structural, magmatic, and metamorphic processes that preceded their entrapment in orogenic belts by continental plate collisions. Ophiolite genetic models appealing to ‘oceanic’ or ‘suprasubduction’ provenance are still unable to reconcile several basic problems, including: (1) the association of boninites with oceanic ridge-type structural settings; (2) the diachronous ‘patch-like’ distribution of ophiolites in orogenic belts; (3) disparate ages between and within their mantle and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(117 citation statements)
references
References 129 publications
6
110
0
1
Order By: Relevance
“…This was followed by a subduction rollback due to the splitting of the nascent arc in a manner similar to that proposed by Flower and Dilek (2003) and Dilek and Flower (2003). The intra-oceanic subduction led to the formation of a metamorphic sole (Mahmood et al, 1995;Searle et al, 1997;Kakar et al, 2014b) followed by the intrusion of off-axis mafic dykes into both the metamorphic sole and the mantle section of the ophiolite, possibly through a slab/asthenospheric window (Lytwyn and Casey, 1995;Celik, 2007; Figure 7c).…”
Section: Tectonic Emplacement Modelsupporting
confidence: 55%
“…This was followed by a subduction rollback due to the splitting of the nascent arc in a manner similar to that proposed by Flower and Dilek (2003) and Dilek and Flower (2003). The intra-oceanic subduction led to the formation of a metamorphic sole (Mahmood et al, 1995;Searle et al, 1997;Kakar et al, 2014b) followed by the intrusion of off-axis mafic dykes into both the metamorphic sole and the mantle section of the ophiolite, possibly through a slab/asthenospheric window (Lytwyn and Casey, 1995;Celik, 2007; Figure 7c).…”
Section: Tectonic Emplacement Modelsupporting
confidence: 55%
“…These models therefore envision discrete and separate tectonic settings of formation for the WMO and EMO separated in time and space. However, most recent studies have shown that this twofold subdivision is not as sharp as previously thought (Bortolotti et al, 2002;Bébien et al, 1998Bébien et al, , 2000Insergueix-Filippi et al, 2000;Manika et al, 1997;Hoeck et al, 2002;Dilek and Flower, 2003;Beccaluva et al, 2005;Koller et al, 2006;Dilek and Morishita, 2009;Saccani and Tassinari, 2015;Saccani et al, 2017).…”
Section: Introductionmentioning
confidence: 81%
“…5(7hb) 163.9 2.1(7hb) ± ± 167.9 2.8(7mu) 171.7 1.7(7hb) 170.8 3.2(7hb) 171.7 1.7(7hb) 165.1 2.7(7hb) ± ± ± ± ± 171 4(11hb) ± 171.8 1.2(7hb) ( ) ± 174.0 2.5 7hb ± 162.1 2.4(7hb) ± 157.2 11.6(7hb) ± 162.9 1.7(7hb) 181.6 1.6(7bi) 169.1 1.6(7mu) ± ± ± 117 1.5(8hb) 118.3 3.1(8hb) 109.6 2.4(8pl) 125 2(10hb) 116.6 3.3(10hb) ± ± ± ± ± 165.7 5.5 (7hb) ± 170. Flower, 2003 andÇelik et al, 2011).…”
Section: H E L L E N I D E Smentioning
confidence: 99%